PELATIHAN PEMBUATAN MENU GIZI SEIMBANG PADA BALITA DI KB/RA DI KECAMATAN JENU KABUPATEN TUBAN - Idcha KR; Nikita WP; Ahmad David RA (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
ABSTRACT Toddlers are a group that shows rapid growth, so they need maximum nutrients. Fulfillment of nutritional needs is an important indicator in the process of growth and development of toddlers. The prevalence of malnutrition and undernutrition under five is 17.7%. The nutritional problem for toddlers is the lack of fulfillment of balanced nutrition caused by a lack of mother's knowledge about nutrition that must be fulfilled by toddlers during their growth period. Based on the problems above, it is necessary to carry out immediate intervention through training on preparing a balanced nutritional menu for children. The purpose of this activity is to help schools, teachers and parents to make healthy food and snack menus for toddlers. It is hoped that after this community service all participants can apply it in daily life to reduce the risk of toddler nutritional problems. Keyword: Nutrition, Toddlers, Balance Nutrition Menu